PENGARUH PERILAKU KEWIRAUSAHAAN TERHADAP KINERJA USAHATANI KARET DI PROVINSI JAMBI - Refaul Khairiyakh; Elwamendri Elwamendri; Dwi Nurul Amalia (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
This study aims to determine the effect of entrepreneurship behavior on the performance of rubber in Jambi Province. This research was conducted in a rubber production center area in Jambi Province. The selected locations are Batanghari and Muaro Jambi Region. The location was chosen purposively with the consideration that the two regions are rubber development areas based on the rubber development masterplan of Jambi Province. Selection of villages was with the same characteristics of sub-districts, and villages that resulted in the largest production of smallholder rubber. The method of analysis that used was Structural Equation Modeling (SEM). SEM analysis is a development or combination of several multivariate techniques. SEM applications are primarily intended to derive structural models. From the results of the study note that the entrepreneurship behavior of farmers affects the performance of rubber farming. The indicator of the latent variable of entrepreneurship that has the greatest value is the acceptance of risk. Meanwhile, the latent variable indicator for farming performance with the biggest loading factor is income.